2006
DOI: 10.1002/ccd.20971
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of embolic particles during percutaneous coronary intervention to stable plaque: It correlates to coronary flow dynamics and myocardial damage

Abstract: Embolic particles are frequently observed during PCI to stable plaque and the majority are liberated after stenting. There appears to be a quantitative relationship between amounts of HITS and coronary microvessel dysfunction and minor myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
0
16
1
Order By: Relevance
“…[4][5][6][7] Distal embolization is one of the strongest contributors to PMI, and embolic particles are frequently observed during PCI. 1,8,9) The amount of microembolization is strongly related to the magnitude of cTn elevation, microvascular dysfunction, and worsening of cardiac function. [8][9][10] Myocardial microvascular function can be evaluated by quantifying the coronary flow reserve (CFR).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Distal embolization is one of the strongest contributors to PMI, and embolic particles are frequently observed during PCI. 1,8,9) The amount of microembolization is strongly related to the magnitude of cTn elevation, microvascular dysfunction, and worsening of cardiac function. [8][9][10] Myocardial microvascular function can be evaluated by quantifying the coronary flow reserve (CFR).…”
mentioning
confidence: 99%
“…1,8,9) The amount of microembolization is strongly related to the magnitude of cTn elevation, microvascular dysfunction, and worsening of cardiac function. [8][9][10] Myocardial microvascular function can be evaluated by quantifying the coronary flow reserve (CFR). 11) A pressure/ temperature sensor-tipped guidewire can measure fractional flow reserve (FFR) and CFR by thermodilution.…”
mentioning
confidence: 99%
“…In previous PCI studies, it was shown that the coronary microembolism is frequently induced directly after balloon deflation and especially after stent implantation. 3,4,23,24 Distal protection systems during transcatheter treatment of aorto-coronary saphenous vein graft stenosis, confirmed the process of coronary microembolization 30 whereas thrombotic and nonthrombotic material with a size from 100 to 550 lm was identified. 6 Microemboli consisting of such thrombotic and non-thrombotic material cause high intensity signals (HITS) within the Doppler velocity spectrum.…”
Section: Introductionmentioning
confidence: 80%
“…10 -12 Microemboli, detected with an intracoronary Doppler guidewire in 27 of 31 patients undergoing PCI, were significantly more common in those with troponin elevation. 10 Although some patients have emboli large enough to occlude a branch vessel large enough to be seen at angiography, the vast majority of emboli are quite small, as are the ischemic territories. 29 Pretreatment with several agents has been shown to decrease biomarker release after PCI in small randomized trials.…”
Section: Discussionmentioning
confidence: 99%